2020
DOI: 10.30574/gscbps.2020.13.1.0284
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of adding boric acid at different doses into mixed feed on fattening performance, carcass characteristics, and bone quality of Japanese quails

Abstract: The aim of this study is to investigate the effects of adding different doses of boric acid (H3BO3) to the mixed feed of Japanese quail (Coturnix coturnix Japonica) on fattening performance, carcass and bone properties. For this purpose, a total of 96 quails aged 15 days were balanced according to their live weight and sex, and 4 trials were randomly divided into groups. Each group is composed of 4 repetitions. Trial groups; the control group (C) given mixed feed, the group with 100 mg / kg boric acid (BA) add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Appropriate levels of jujube as a supplement or substitute can improve feed palatability, feed intake, nutrient digestibility, reduce the rate of feed conversion to gain, and improve the gut microbiome and the quality of animal products (Xu et al 2022). It has been reported that the daily feed intake of quails is between 25-30 g (Simsek et al 2020), and similar results were obtained in this study. This study found that the highest feed intake was 29.37 g in the T2 group.…”
Section: Laying Performancesupporting
confidence: 88%
“…Appropriate levels of jujube as a supplement or substitute can improve feed palatability, feed intake, nutrient digestibility, reduce the rate of feed conversion to gain, and improve the gut microbiome and the quality of animal products (Xu et al 2022). It has been reported that the daily feed intake of quails is between 25-30 g (Simsek et al 2020), and similar results were obtained in this study. This study found that the highest feed intake was 29.37 g in the T2 group.…”
Section: Laying Performancesupporting
confidence: 88%